Effective Pro-Inflammatory Induced Activity of GALT, a Conserved Antigen in A. Pleuropneumoniae, Improves the Cytokines Secretion of Macrophage via p38, ERK1/2 and JNK MAPKs Signal Pathway - Zhang, Fei; Zhao, Qin; Tian, Jin; Chang, Yung-Fu; Wen, Xintian; Huang, Xiaobo; Wu, Rui; Wen, Yiping; Yan, Qigui; Huang, Yong; Ma, Xiaoping; Han, Xinfeng; et al. (Frontiers in Cellular and Infection Microbiology, 2018)
Abstract: GALT is a highly conserved antigen in gram-negative bacteria, and has been shown to play a crucial role in the pathogenesis of many zoonoses. Actinobacillus pleuropneumoniae (APP) is a widespread respiratory system pathogen belonging to the Pasteuriaceae family. The functional mechanisms of GALT in the process of infection remain unclear. The aim of this study is to analyze roles of GALT in the pathogenesis of APP infection. Recombinant GALT was expressed in E. coli, purified, and was used to treat a Raw 264.7 macrophage line. Stimulation of Raw 264.7 macrophages with recombinant GALT protein induced the expression of pro-inflammatory cytokines (TNF-α, IL-1β and IL-6). Compared with negative control, GALT led to increased production of pro-inflammatory cytokines in treated cells. Furthermore, specific inhibitors of the extracellular signal-regulated P38 and JNK MAPKs pathways significantly decreased GALT-induced pro-inflammatory cytokine production, and a western blot assay showed that GALT stimulation induced the activation of the MAPKs pathway. This process included cell-signaling pathways like P38, ERK1/2 and JNK MAPKs and NF-κB. Both TLR2 and TLR4 were receptors of GALT antigens, whereas they played negative and positive roles (respectively) in the process of induction and expression of pro-inflammatory cytokines. Taken together, our data indicate that GALT is a novel pro-inflammatory mediator and induces TLR2 and TLR4-dependent pro-inflammatory activity in Raw 264.7 macrophages through P38, ERK1/2 and JNK MAPKs pathways.